Impact of Bariatric Surgery on Circulating Metabolites and Cognitive Performance - Pino, Jessica M. V.; Silva, Vitória F.; Campos, Raquel M. S.; Mônico-Neto, Marcos; de Araujo, Kaique A.; Seva, Danielle C.; Kato, Melissa Y.; Galvão, Thales D.; Bitterncourt, Lia R. A.; Tufik, Sergio; Lee, Kil S. (Obesity surgery, 2024)
Introduction Bariatric surgery is an effective intervention to reduce obesity and improve associated comorbidities. However, its effects on cognitive function are still the subject of debate. Given that the bioavailability of circulating metabolites can influence brain metabolism and cognitive performance, we aimed to assess the effects of bariatric surgery on plasma metabolic profiles and cognitive performance. Methods We recruited 26 women undergoing gastric bypass surgery. We conducted anthropometric assessments and collected plasma samples for metabolomic analysis. A set of 4 cognitive tests were used to evaluate cognitive performance. Participants were reevaluated 1 year post-surgery. Results After surgery, attention capacity and executive function were improved, while immediate memory had deteriorated. Regarding metabolic profile, reduction of beta-tocopherol and increase of serine, glutamic acid, butanoic acid, and glycolic acid were observed. To better understand the relationship between cognitive function and metabolites, a cluster analysis was conducted to identify more homogeneous subgroups based on the cognitive performance. We identified cluster 1, which did not show changes in cognitive performance after surgery, and cluster 2, which showed improved attention and executive function, but reduced performance in the immediate memory test. Thus, cluster 2 was more homogeneous group that replicated the results of non-clustered subjects. Analysis of the metabolic profile of cluster 2 confirmed serine, glutamic acid, and glycolic acid as potential metabolites associated with cognitive performance. Conclusions Metabolites identified in this study have potential for biomarkers and alternative therapeutic target to prevent obesity-related cognitive decline. Key points • Attention capacity and executive function were improved 12 months post bariatric surgery. • Immediate memory was worsened 12 months post bariatric surgery. • Serine, glutamic acid, and glycolic acid are potential metabolites linked to the alteration of cognitive performance. Graphical Abstract